Pengaruh Skeptisisme Profesional Audit dan Keahlian Auditor Terhadap Kualitas Audit - Ruci Arizanda Rahayu (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the effect of Audit Professional Skepticism and Auditor Expertise on Audit Quality. The analytical tool used is to tabulate the questionnaire, collect data in the form of validity and reliability tests. The hypothesis in this study is that there is an effect of the Professional Skepticism of the Audit and the Expertise of the Auditor on Audit Quality. To test this hypothesis, the SPSS data analysis tool was used. The results obtained based on the validity test show that all statements in the questionnaire are declared valid. For the reliability test of all variables, the composite reliability value or Crobach's alpha value was stated to be reliable. And for Hypothesis Test based on R-Square, T-Statistics and Significance Value shows that all hypotheses are accepted. The results of this hypothesis state that professional audit skepticism and auditor expertise have an effect on audit quality.